Administrative competencies in many of Iraqi public Organizations: comparative study. - سلمان, فاضل حمد (Journal of Economics and Administrative Sciences, 2012)
Competencies topic in general , and Administrative competencies in specific, are considered as important subject in the contemporary administrative literature in all countries as well as in public and privet Organizations. For this reason, we have need to study those competencies in many Iraqi Organizations.Two Organizations wer chosen for this research one of them is the Institution of taxation, and the other is the General company of Electric the data and information related to the research have been collected by desined questioner which has been given to a sample of (50) persions divided eqully between the two maintioned organizations. The results of the study had differences the research hypotheses in which there were differs significant  between competences in the above mentioned  Organizations. Some of competences which are existed in the Institution of taxation are more significant than those existed in the General company of Electric and vice versa. For many other competencies, there are no significant differences between the two maintained Organizations.At the end of the research, many recommendations wer given to enhance the effectiveness of competences in both Organizations. The main proposal recomanded that both Organizations have to put an active system to motivate employees to develop their competences.